Negative experiences of pain and withdrawal create barriers to abscess care for people who inject heroin. A mixed methods analysis. (1st September 2018) - Summers, Phillip J.; Hellman, Julia L.; MacLean, Madison R.; Rees, Vaughan W.; Wilkes, Michael S.
Highlights: 66% of people who inject heroin experienced skin and soft tissue infection. 38% reported delaying care for infections by two weeks or more. Pain and withdrawal are prominent reasons for delaying and terminating care early. Unaddressed pain and withdrawal symptoms contribute to negative care experiences. Negative care experiences are a strong motivator for not engaging in future care. Abstract: Background: Skin and soft tissue infections (SSTIs) are prevalent among people who inject heroin (PWIH). Delays in seeking health care lead to increased costs and potential mortality, yet the barriers to accessing care among PWIHs are poorly understood. Methods: We administered a quantitative survey (N = 145) and conducted qualitative interviews (N = 12) with PWIH seeking syringe exchange services in two U.S. cities. Results: 66% of participants had experienced at least one SSTI. 38% reported waiting two weeks or more to seek care, and 57% reported leaving the hospital against medical advice. 54% reported undergoing a drainage procedure performed by a non-medical professional, and 32% reported taking antibiotics that were not prescribed to them. Two of the most common reasons for these behaviors were fear of withdrawal symptoms and inadequate pain control, and these reasons emerged as prominent themes in the qualitative findings. These issues are often predicated on previous negative experiences and exacerbated by stigma and an asymmetrical power dynamic with providers, resulting in perceived barriers to seeking and completing care for SSTIs. Conclusions: For PWIH, unaddressed pain and withdrawal symptoms contribute to profoundly negative health care experiences, which then generate motivation for delaying care SSTI seeking and for discharge against medical advice. Health care providers and hospitals should develop policies to improve pain control, manage opioid withdrawal, minimize prejudice and stigma, and optimize communication with PWIH. These barriers should also be addressed by providing medical care in accessible and acceptable venues, such as safe injection facilities, street outreach, and other harm reduction venues.